Estudo dos alcaloides quinolônicos de Waltheria brachypetala Turcz: isolamento, determinação estrutural, biogênese, atividades fungitóxica e anticolinesterase - Lima, Murilo Marinho de Castro (Universidade Federal de São Carlos, 2012)
Waltheria brachypetala Turcz (Malvaceae) is an endemic medicinal plant from brazilian northeast. This plant is commonly used on folk medicine as antifungal, antiinflamatory and to treatment of bronchitis and central nervous system disturbs. The aim of this work was the investigation of quinolone alkaloids produced by this plant. Through usual chromatographic methods of purification were isolated from hexane and diclorometane phases of roots and bark, nineteen quinolone alkaloids, being ten already reported on literature: antidesmone (1), N-methyl-antidesmone (2), desoxi-antidesmone (3), chamaedrone (4), hyeronimone (5), metil-hyeronimone (6), waltheriones A (7) and B (8), N-methyl-waltherione A (9), 4-O-methyl-waltherione A (10) and nine novel alkaloids: waltheriantidesmone (11), brachytelones A (12), B (13), C (14), D (15), waltheriones C (16) and D (17), N-methyl-waltherione B (18) and 10-hydroxi-waltherione D (19), along with common ciclycpeptides to Hermannieae. Were also isolated twocoumarinolignans cleomicine A (20) and acethylcleomicine A (21) as new to genus Waltheria, and other secondary metabolites common in plants. The hexane and dicloromethane phases of the bark were studied by HPLC-UV-MS/MS to make possible the identification of the probable biogenesis intermediates of the waltheriones: 9,10-epoxy-10-hydroxi-melochinone (22), 13-hydroxi-melochinone (23) e melochinone (24), along with vanessine (25) e waltheriahyeronimone (26), being 26 did not yet report on literature. The isolation of that alkaloids from W. brachypetala confirmes it as potential chemossistematic markers to Hermannieae tribe and it strengthens the hypothesisof chemossystematic to suggest possible evolutive similarity between Hermannieae (Malvaceae) and Antidesmeae (Phyllantaceae), as well as similarity of antidesomne biogenesis pathway with melochinone derivatives biogenesis pathway. The alkaloids11, 12 and 13 represent a new class of aryl-alkyl-quinolone alkaloids that are being reported by first time in this work. The biological potential of W. brachypetalawas evaluated on the inhibition of AChE enzime and fungitoxic assays against the citros phytopatogen Guignardia citricarpa. All quinolone alkaloids tested presented significant activity of inhibition of AChE in vitro detaching the aryl-alkyl-quinolone alkaloids: waltheriantidesmone, brachytelone A e brachytelone B, that inhibits AChE in 93%, 88,04% e 91,05%, respectively, on concentration of 100 μM and with low value of IC50. The alkaloids antidesmone, w-antidesmone, chamaedrone, brachytelone A and brachytelone B, apresentaram excelente fungitoxic activity against G. citricarpa, as much with regard to mycelial growth inhibition as to germination of spores and apressorium formation presenting low value ofIC50. It detaches that the alkaloids brachytelone A and waltheriantidesmone presented more potente than the commercial fungicide carbendazin at concentration of 5 μg/ml, being thus potential candidates to chemical control of the Black Spot of Citros.
Study of quinolone alkaloids from Waltheria brachypetala Turcz. (Malvaceae): isolation, structural elucidation, biogenesis and fungitoxical and anticholinesterase activities
Keywords: Produtos naturais; Alcalóides; Biogênese; Quimiossistemática; Atividades biológicas; Natural products; Alkaloids; Biogenesis; CIENCIAS EXATAS E DA TERRA::QUIMICA